OSTEOPOROSIS IN A SEVENTH YEAR OLD BOY WITH ACUTE LYMPHOBLASTIC LEUKEMIA (Case Report) - Salim, H; Ariawati, K.; Bikin-Suryawan, W.; Arimbawa, and I. M. (BALI MEDICAL JOURNAL, 2013)
Osteoporosis in children is rare and usually secondary to an underlying disease process whose diagnosis may be difficult to detect. It can be a manifestation of acute lymphoblastic leukemia (ALL). About a-quarters of children with ALL will have signs and symptoms of osteoporosis. We report the case of a seventh-year-old boy with back pain. His antero-posterior pelvic radiograph showed the osteoporotic bone. The bone age study revealed six-year-old bone. Review of peripheral blood smear showed normochromic anemia with thrombocytopenia. Immunophenotyping of peripheral blood revealed no dominant marker was seen, but the bone marrow aspiration confirms the diagnosis of ALL (L2).